The upside of unrequited - Albertalli, Becky (Balzer + Bray, an imprint of HarperCollinsPublishers, 2017)
Seventeen-year-old Molly Peskin-Suso knows all about unrequited love. No matter how many times her twin sister, Cassie, tells her to woman up, Molly can't stomach the idea of rejection. So she's careful. Fat girls always have to be careful. Then a cute new girl enters Cassie's orbit, and for the first time ever, Molly's cynical twin is a lovesick mess. Meanwhile, Molly's totally not dying of loneliness -- except for the part where she is. Luckily, Cassie's new girlfriend comes with a cute hipster-boy sidekick. If Molly can win him over, she'll get her first kiss and she'll get her twin back. There's only one problem: Molly's coworker, Reid. He's a chubby Tolkien superfan with a season pass to the Ren Faire, and there's absolutely no way Molly could fall for him. Right?